PENGARUH SUMBER BAHAN ORGANIK YANG BERBEDA TERHADAP KUALITAS PEMBUATAN MIKROORGANISME LOKAL (MOL) - Julianus Jeksen; Charly Mutiara (Agriculture Faculty of Flores University, 2018)
This study aims to determine the content of microorganisms from local microorganisms and determine their quality. This research is a descriptive study, where the results of the analysis of microbial content are described by the standard microbial content in Local Microorganisms. The results showed that Local Microorganisms from the leaves of Kirinyu, Gamal, Lamtoro and vegetables wastes contained Lactobacillus, Saccharomyces mushrooms, Actinomycetes fungi, and phosphate solvent bacteria (BPF). Local microorganisms from these materials have not been able to produce good quality because they are still lower than the minimum technical requirements based on Minister of Agriculture Regulation number 70 of 2011, while Saccharomyces mushroom microorganism content, pH and phosphate solvent bacteria (BPF) are in accordance with technical requirements all types of local microorganisms positively contain phosphate solvent bacteria (BPF).